Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/1472-6963-14-207
|View full text |Cite
|
Sign up to set email alerts
|

Cost and burden of informal caregiving of dependent older people in a rural Indian community

Abstract: BackgroundLack of state supported care services begets the informal caregiving by family members as the mainstay of care provided to the dependent older people in many Low and Middle Income Countries (LMICs), including India. Little is known about the time spent on caregiving, its cost and the burden experienced by these informal caregivers. We aimed to estimate the costs of informal caregiving and to evaluate the nature as well as correlates of caregivers’ burden in a rural Indian community.MethodsWe assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 46 publications
3
70
1
1
Order By: Relevance
“…About one third patients in our survey reported to have paid help available however as this was a self-reported, non-descriptive questionnaire we are not able to comment on the type of help however having maids for domestic help in Karachi and other urban areas is very common and available at low wages; it is highly likely that these are unprofessional and untrained domestic workers. This scenario may be completely different in low socio-economic and rural areas of Pakistan, as also reported in a study in rural India with 0% of people having paid help available [27]. These are informal and untrained caregivers and have limited understanding of dementia symptoms.…”
Section: Variablesmentioning
confidence: 94%
“…About one third patients in our survey reported to have paid help available however as this was a self-reported, non-descriptive questionnaire we are not able to comment on the type of help however having maids for domestic help in Karachi and other urban areas is very common and available at low wages; it is highly likely that these are unprofessional and untrained domestic workers. This scenario may be completely different in low socio-economic and rural areas of Pakistan, as also reported in a study in rural India with 0% of people having paid help available [27]. These are informal and untrained caregivers and have limited understanding of dementia symptoms.…”
Section: Variablesmentioning
confidence: 94%
“…In support of the literature , older caregivers, in addition to caring for elderly individuals, were found to be significantly associated with weaker enabling variables, including access to health care, income and family support. Additionally, in support of the previous findings , they were found to be significantly associated with lower healthy life indicators, including sleep quality, energy level, concentration and decision‐making.…”
Section: Discussionmentioning
confidence: 54%
“…Brinda et al found that 63.5% of caregivers in their study were unhappy with the function of giving care. 25 Providing care affects the physical, emotional of caregivers. Thus, declining wellbeing of caregivers can lead to be unhappiness.…”
Section: Discussionmentioning
confidence: 99%